Biogerontology, “Anti-aging Medicine,” and the Challenges of Human Enhancement - Juengst, Eric T. (The Hastings Center report, 2003)
Slowing the aging process would be one of the most dramatic and momentous ways of enhancing human beings. It is also one that mainstream science is on the brink of pursuing. The state of the science, together with its possible impact, make it an important example for how to think about research into all enhancement technologies.